Sistem Fotobioreaktor dilengkapi Pemantauan Konsentrasi CO2 dari Kabut Asap pada Model Kebakaran Lahan Gambut - Azzahra Zhuhrii; Harmadi Harmadi (Universitas Andalas, 2024)
Indonesia's peatlands are quite extensive and often cause fires that lead to haze. Haze contains harmful compounds, namely carbon dioxide (CO2). One of the efforts to reduce CO2 content is using a microalgae Chlorella vulgaris photobioreactor system. This research makes a photobioreactor system equipped with monitoring the concentration of CO2 emissions from haze on a peatland fire model. The photobioreactor is equipped with an MQ-135 sensor to detect CO2 concentration and an LM35 sensor to determine changes in temperature in the microalgae container. The temperature in the microalgae container is set in the range of 25ºC30ºC according to the habitat of microalgae. The output data from the sensors is processed by Arduino Uno R3. The measurement results of CO2 concentration and temperature are displayed on the I2C LCD in units of ppm and ºC. This study uses a variety of light sources in the form of red, green, blue LEDs and sunlight. The results of the study found that blue LED lights play a more active role to increase the ability of microalgae to reduce CO2 emissions in the room. The photobioreactor system using Chlorella vulgaris microalgae is able to reduce the concentration of CO2 produced from haze in the peatland fire model of 655.08 ppm down to 620.47 ppm within 1 hour.